Pengaturan Pengawasan Penggunaan Cryptocurrency untuk Mencegah Tindak Pidana Pencucian Uang - Oktaviano Parulian Sugiharto Widjoyo; Yovita Arie Mangesti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the regulation and supervision of cryptocurrency use in preventing money laundering by employing a normative juridical method through the analysis of legislation, legal doctrines, and court decisions, including the Indra Kenz case as a concrete example of legal application. The findings reveal that Indonesia’s regulatory framework for digital assets remains fragmented, creating uncertainty in law enforcement, particularly regarding blockchain transaction tracing, compliance obligations for Virtual Asset Service Providers (VASPs), and the explicit recognition of digital assets as criminal objects. These conditions underscore the need for regulatory harmonization and integrated oversight to strengthen preventive and repressive measures against cryptocurrency-based money laundering.